Analisis Pengaruh Hollow Glass Spheres (HGS) Terhadap Karakteristik Rheologi Suspensi Lightweight Cement Sumur Dangkal - Algi Setiawan; Elfisius Geron; Yedi Saputra Junior (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Shallow gas well cementing risks gas migration and lost circulation due to low fracture gradients. This study analyzes the effects of Hollow Glass Spheres (HGS) additives on the rheological parameters of a 11.67 ppg Class G cement slurry. Testing based on API RP 10B-2 standards was conducted under BHCT 142°F at Jasa Energi Nasional, Balikpapan. Results showed Sample 1 (HGS System) yielded a Plastic Viscosity of 61.5 cP, a Yield Point of 14.5 lb/100 ft², and a 10-Minute Gel Strength of 16.00 lb/100 ft² as a reliable anti-segregation agent. Conversely, Sample 2 (Baseline) induced a weak gel (11.00 lb/100 ft²) that triggers particle settling. HGS effectively optimizes the flowability of ultra-lightweight cement slurries to remain pumpable.